Unsur Direncanakan Pada Pasal 340 Kitab Undang-Undang Hukum Pidana Dalam Putusan Pengadilan Tinggi Tanjung Karang Nomor 145/Pid/2020/PT Tjk - Niken Febriana Dwi; Ade Adhari (Universitas Ekasakti, 2024)
This study aims to analyze the fulfillment of the planned elements in Article 340 of the Criminal Code against the Tanjung Karang High Court Decision Number 145 / Pid / 2020 / Pt Tjk. Where the Judge in deciding this case explained that the planned element was not fulfilled on the grounds that the actions committed by the defendant were spontaneous. The research method used is: normative juridical legal research conducted with literature studies or secondary data as a basis for researching by conducting searches of regulations and literature related to the problem under study. The data collected is then processed and explained descriptively so that the relationship of data with one another can be described factually. The results of the study showed: that in the Tanjung Karang High Court Decision Number 145 / Pid / 2020 / PT Tjk, the judge decided the defendant Edi Antoni alias Edi Recing bin Kemis using Article 338 of the Criminal Code, which was previously the defendant through Kalianda District Court Decision Number 209 / Pid.B / 2020 / PN Kla the defendant received a verdict for participating in murder. In the appeal process at the Tanjung karang High Court, the defendant can be convicted using Article 340 of the Criminal Code concerning Premeditated Murder because of the fulfillment of the premeditated element in Article 340 of the Criminal Code, it can be proven by the defendant admitting he was conscious when committing his act and wanted the death of the victim and the defendant could not prove the origin of the knife used to commit the murder.